Laser Direct‐Write Onto Live Tissues: A Novel Model for Studying Cancer Cell Migration. Issue 11 (15th March 2016) - Burks, Hope E.; Phamduy, Theresa B.; Azimi, Mohammad S.; Saksena, Jayant; Burow, Matthew E.; Collins‐Burow, Bridgette M.; Chrisey, Douglas B.; Murfee, Walter L.
Abstract : Investigation into the mechanisms driving cancer cell behavior and the subsequent development of novel targeted therapeutics requires comprehensive experimental models that mimic the complexity of the tumor microenvironment. Recently, our laboratories have combined a novel tissue culture model and laser direct‐write, a form of bioprinting, to spatially position single or clustered cancer cells onto ex vivo microvascular networks containing blood vessels, lymphatic vessels, and interstitial cell populations. Herein, we highlight this new model as a tool for quantifying cancer cell motility and effects on angiogenesis and lymphangiogenesis in an intact network that matches the complexity of a real tissue. Application of our proposed methodology offers an innovative ex vivo tissue perspective for evaluating the effects of gene expression and targeted molecular therapies on cancer cell migration and invasion. J. Cell. Physiol. 231: 2333–2338, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Investigation into the mechanisms driving cancer cell behavior and the subsequent development of novel targeted therapeutics requires comprehensive experimental models that mimic the complexity of the tumor microenvironment. In this article, we highlight a new model that combines laser direct‐write, a form of bioprinting, with a tissue culture model to spatially position single or clustered cancer cells onto ex vivo microvascular networks containing blood vessels, lymphatic vessels, and interstitial cell populations. Application of our proposed methodology offers an innovative ex vivo tool for evaluating the effects of gene expression and targeted molecular therapies on cancer cell migration and invasion.